The hydraulics of local separation applied to middle layer upwelling at the exit of Shelikof Strait, northwest Gulf of Alaska - Nan Yuan; Humio Mitsudera; Hideharu Sasaki (Ocean Dynamics, 2026)

Iron dynamics during spring phytoplankton bloom in the southern Sea of Okhotsk: The impact of sea ice melt on iron supply - Momoka Imai; Aiko Murayama; Kazuya Ono; Youhei Yamashita; Koji Suzuki; Tomohiro Nakamura; Kay I. Ohshima; Humio Mitsudera; Jun Nishioka (Progress in Oceanography, 2026)

Northbound movement of northern fur seal (Callorhinus ursinus) and their response to the oceanographic features - Heping Li; Ryo Dobashi; Humio Mitsudera; Yoko Mitani (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Kuroshio surface water intrusion into the eastern part of the transition domain: its pathways and decadal variations - Takuro Matsuta; Humio Mitsudera; Toru Miyama; Hiroyuki Tomita (Journal of Oceanography, 2025)

High-turbidity bottom mixed-layer water on the shelf off Hokkaido in the Okhotsk Sea: distribution, seasonal variations, and spreading - Tomohiro Nakamura; Junki Ueda; Tokihiro Kono; Jun Nishioka; Humio Mitsudera; Kaoru Ito (Journal of Oceanography, 2025)

Enhanced eddy activity along the Subantarctic Front under intensified westerly winds - Takuro Matsuta; Humio Mitsudera; Yukio Masumoto; Hideharu Sasaki; Ryo Furue; Tomomichi Ogata (Ocean Dynamics, 2024)

Long-term observation of the Soya Warm Current using HF ocean radars: relationship between the Soya Warm Current variability and the sea level anomalies in the Soya/La Perouse Strait - Naoto Ebuchi; Yasushi Fukamachi; Kay I. Ohshima; Humio Mitsudera; Jun Nishioka; Toru Takatsuka; Kazuya Ono; Masao Ishikawa; Takaharu Daibo; Kunio Shirasawa; Masaaki Wakatsuchi (Journal of Oceanography, 2024)

Kuroshio water intrusion into the subarctic region in the western North Pacific Ocean and analyses of the Lagrangian coherent structure - Takuro Matsuta; Humio Mitsudera (Journal of Oceanography, 2023)
Previous studies have suggested that the quasi-stationary jets, sometimes called the “Isoguchi jets” in the western North Pacific Ocean, regulate the warm and salty conditions in the transition domain between the Subarctic Boundary and the Subarctic Front. Here, we show that mesoscale eddies and interannual/decadal modulations are responsible for the Kuroshio water intrusion into the transition domain. A case study using the Lagrangian coherent structure suggests that the northward shift of the Kuroshio Extension forms a favorable velocity field for the Kuroshio water intrusion around the Subarctic Boundary, while the geometric structure inside the Isoguchi jet is quasi-permanent.

A study of the simulated climatological January mean upwelling in the northwestern Gulf of Alaska - Nan Yuan; Humio Mitsudera; Hideharu Sasaki (Ocean Dynamics, 2023)
In this research, we studied the upwelling in the northwestern Gulf of Alaska using the climatological January mean and data from the output of the Ocean General Circulation Model for Earth Simulator (OFES2). Specifically, we analyzed the upwelling in the regions where the Alaska Coastal Current (ACC) flows out of the Shelikof Strait (especially the part to the west of Kodiak Island) and where the ACC and the Alaskan Stream (AS) are confluent. In both regions, strong geostrophic currents and downwelling-favorable wind predominate in winter. Furthermore, there are freshwater discharges along the Alaskan coast and an observed mean current vertical shear in the ACC. We revealed that when the internal water stress is larger than the wind stress inside the study regions, this could be decisive in terms of the local horizontal velocity divergence and further upwelling, even if the region is away from the coast and lacks upwelling-favorable wind conditions. Geostrophic stress is part of the internal water stress and is a product of the geostrophic current shear (due to the thermal wind relation) and the vertical viscosity coefficient. The analysis indicated that a front with a large geostrophic stress may act as a “virtual wall” and contribute to local upwelling within a depth of approximately 100 m in the study regions. This process could provide a heuristic for understanding the distribution of pollock in the areas during February and March, which corresponds to the simulated upwelling region.

Cross-shelf overturning in geostrophic-stress-dominant coastal fronts - Nan Yuan; Humio Mitsudera (Journal of Oceanography, 2023)
Compared to the dynamics of the predominantly geostrophic along-shelf current, our understanding of the cross-shelf dynamics in the Sea of Okhotsk is inadequate despite their importance in water mixing and nutrient entrainment. We investigated the cross-shelf overturning circulation along the East Sakhalin Current, which is a source of nutrients such as iron for the western North Pacific. Here, we reveal that the cross-shelf circulation during winter is characterised by a nearshore upwelling and a shelf-break downwelling under a downwelling-favourable monsoon wind, contrary to a classical Ekman overturning (EOT). This reverse EOT is driven by the internal water stress, which is caused by intensive vertical mixing and geostrophic vertical shear in the shelf-break front produced by riverine discharges from the far-eastern Eurasian Continent. The EOT blocks the Ekman onshore transport from the open ocean, thereby producing a deep mixed layer at the shelf break. Scaling analyses indicate the applicability of this mechanism to various other shelf-break fronts.

Nutrient and dissolved inorganic carbon variability in the North Pacific - Sayaka Yasunaka; Humio Mitsudera; Frank Whitney; Shin-ichiro Nakaoka (Journal of Oceanography, 2021)
A compilation of surface water nutrient (phosphate, nitrate, and silicate) and partial pressure of CO 2 ( p CO 2 ) observations from 1961 to 2016 reveals seasonal and interannual variability in the North Pacific. Nutrients and calculated dissolved inorganic carbon (DIC) reach maximum concentrations in March and minimum in August. Nutrient and DIC variability is in-phase (anti-phase) with changes in the mixed layer depth (sea surface temperature) north of 30 °N, and it is anti-phase (in-phase) with changes in Chl-a north of 40 °N (in 30 °N–40 °N). Seasonal drawdown of nutrients and DIC is larger toward the northwest and shows a local maximum in the boundary region between the subarctic and subtropics. Stoichiometric ratios of seasonal drawdown show that, compared to nitrate, silicate drawdown is large in the northwestern subarctic including the Bering and Okhotsk seas, and drawdown of carbon is larger toward the south. Net community production in mixed layer from March to July is estimated to be more than 6 gC/m 2 /mo in the boundary region between the subarctic and subtropics, the western subarctic, the Gulf of Alaska, and the Bering Sea. Nutrient and DIC concentrations vary with the Pacific Decadal Oscillation and the North Pacific Gyre Oscillation which cause changes in horizontal advection and vertical mixing. The DIC trend is positive in all analysis area and large in the western subtropics (> 1.0 μmol/l/yr). Averaged over the analysis area, it is increasing by 0.77 ± 0.03 μmol/l/yr (0.75 ± 0.02 μmol/kg/yr).

The 9th International Workshop on Modeling the Ocean (IWMO 2017) in Seoul, Korea, July 3–6, 2017 - Lie-Yauw Oey; Yign Noh; Jarle Berntsen; Sung Yong Kim; Humio Mitsudera; Tal Ezer (Ocean Dynamics, 2020)

Buoyancy shutdown process for the development of the baroclinic jet structure of the Soya Warm Current during summer - Tatsuro Karaki; Humio Mitsudera; Hiroshi Kuroda (Journal of Oceanography, 2018)

“Hot Spots” in the climate system—new developments in the extratropical ocean–atmosphere interaction research: a short review and an introduction - Hisashi Nakamura; Atsuhiko Isobe; Shoshiro Minobe; Humio Mitsudera; Masami Nonaka; Toshio Suga (Journal of Oceanography, 2015)

Oceanic fronts and jets around Japan: a review - Shinichiro Kida; Humio Mitsudera; Shigeru Aoki; Xinyu Guo; Shin-ichi Ito; Fumiaki Kobashi; Nobumasa Komori; Atsushi Kubokawa; Toru Miyama; Ryosuke Morie; Hisashi Nakamura; Tomohiro Nakamura; et al. (Journal of Oceanography, 2015)

A preliminary study to understand the transport process for the eggs and larvae of Japanese Pacific walleye pollock Theragra chalcogramma using particle-tracking experiments based on a high-resolution ocean model - Hiroshi Kuroda; Daisuke Takahashi; Humio Mitsudera; Tomonori Azumaya; Takashi Setou (Fisheries Science, 2014)

Particle-tracking simulation for the drift/diffusion of spilled oils in the Sea of Okhotsk with a three-dimensional, high-resolution model - Jun Ono; Kay I. Ohshima; Keisuke Uchimoto; Naoto Ebuchi; Humio Mitsudera; Hajime Yamaguchi (Journal of Oceanography, 2013)

A new climatology of the Okhotsk Sea derived from the FERHRI database - Hiroki Uehara; Andrey A. Kruts; Yuriy N. Volkov; Tomohiro Nakamura; Tsuneo Ono; Humio Mitsudera (Journal of Oceanography, 2012)

New developments in mode-water research: an introduction - Shang-Ping Xie; Atsushi Kubokawa; Fumiaki Kobashi; Humio Mitsudera (Journal of Oceanography, 2012)

The cyclonic circulation in the Australian–Antarctic basin simulated by an eddy-resolving general circulation model - Shigeru Aoki; Yoshikazu Sasai; Hideharu Sasaki; Humio Mitsudera; Guy D. Williams (Ocean Dynamics, 2010)

Numerical experiments of air–ice drag coefficient and its impact on ice–ocean coupled system in the Sea of Okhotsk - Ayumi Fujisaki; Hajime Yamaguchi; Humio Mitsudera (Ocean Dynamics, 2010)

Anticyclonic eddy caused by the Soya Warm Current in an Okhotsk OGCM - Keisuke Uchimoto; Humio Mitsudera; Naoto Ebuchi; Yasumasa Miyazawa (Journal of Oceanography, 2007)

Significance of High-Frequency Wind Forcing in Modelling the Kuroshio - Takuji Waseda; Humio Mitsudera; Bunmei Taguchi; Kunio Kutsuwada (Journal of Oceanography, 2005)

Monitoring the Kuroshio Extension with Dynamically Constrained Synthesis of the Acoustic Tomography, Satellite Altimeter and in situ Data - Konstantin V. Lebedev; Max Yaremchuk; Humio Mitsudera; Iwao Nakano; Gang Yuan (Journal of Oceanography, 2003)

Optimal Basis from Empirical Orthogonal Functions and Wavelet Analysis for Data Assimilation: Optimal Basis WADAi - Takuji Waseda; Leland Jameson; Humio Mitsudera; Max Yaremchuk (Journal of Oceanography, 2003)

Chaotic Advection of the Shallow Kuroshio Coastal Waters - Takuji Waseda; Humio Mitsudera (Journal of Oceanography, 2002)